PENGARUH BANTUAN INTERNATIONAL MONETARY FUND (IMF) TERHADAP KETAHANAN PANGAN PAKISTAN - Ardianti, Eldara; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pakistan has applied for a financial loan from an IMF institution backed by deteriorating economic conditions. The IMF approved the request for assistance after going through various discussions and certain considerations. Financial assistance from the IMF is accompanied by the terms of the policies needed for these conditions. One of them is liberalization of the agricultural sector.This research was analyzed using a structuralism perspective and supported by dependency theory and neoliberalism theory within the scope of international political economy studies. The formulation of all arguments, facts, and theoretical frameworks in this research is guided by the method of qualitative explanation. The data collection technique in this study is through literature study. Data is obtained and collected through journals, books, research papers, news articles, official publications, conference papers, and later from internet pages that have been related in this case research.One of the implementations of the liberalization policy by Pakistan was done by removing subsidies. Such as subsidy of agricultural inputs and domestic food prices. Liberalization also requires that the government's role in controlling food supply be reduced. With various factors influencing, the policies taken by Pakistan on the recommendations of the IMF, they have a negative influence on the problem of Pakistan's food security.Keywords: IMF, agricultural liberalization, food security, Pakistan